Network Effects and Economic Value Creation in Cryptocurrency Ecosystems - Ruben M Nayve Jr; Ferdinand Timbang; Mark Anthony Pelegrin (Universitas 17 Agustus 1945 Surabaya, 2025)
This study investigates the role of network effects in shaping economic value creation within cryptocurrency ecosystems. While cryptocurrencies have evolved from speculative assets into complex digital platforms that facilitate transactions, decentralized finance, and governance, their economic sustainability is fundamentally driven by the dynamics of user adoption and interconnectivity. Drawing upon theories of network externalities and digital platform economics, this research employs a mixed-methods approach that integrates quantitative econometric modeling with qualitative analysis of policy and industry practices. Quantitative data, including market capitalization, transaction volume, wallet addresses, and hash rate, are analyzed to measure the correlation between network growth and value creation. Complementary qualitative insights are derived from literature reviews and expert interviews to contextualize the findings within broader regulatory and technological frameworks. The results reveal that network size and user activity exert significant positive effects on value creation, with evidence of nonlinear threshold dynamics: once a critical mass of adoption is reached, economic value accelerates disproportionately. Comparative analysis across major ecosystems such as Bitcoin and Ethereum highlights differences in how network effects interact with technological innovation and governance structures. The findings contribute to advancing theoretical understanding of digital network economies and provide practical insights for stakeholders, including developers, investors, and policymakers. By identifying both opportunities and risks, particularly regarding volatility and regulatory challenges, this study offers a comprehensive framework for evaluating the long-term sustainability of cryptocurrency ecosystems.